SUSTAINABILITY OF CONSTRUCTION AND DEMOLITION WASTE IN ASTANA, KAZAKHSTAN: COSTS AND RECOVERY POTENTIAL FOR TWO LIFECYCLE SCENARIOS. - Kassymov, Amirlan (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Construction sector is one of the biggest contributors towards the global carbon emissions and one of the main sectors in the economy of Kazakhstan. Currently, the vast majority of construction projects in Kazakhstan follow the linear economy pattern, i.e extract raw materials at the beginning of the project, and dispose of construction and demolition waste to the landfill after the end-of-life of the building. However, there is a global trend in the construction sphere towards pivoting from linear to circular economy approach, i.e towards closing of the loops of materials production via utilization of construction and demolition waste materials in new construction projects. This research is focused on the comparison of linear and circular economy scenarios in terms of direct costs and social cost of carbon (SCC) associated with the end-of-life scenarios of two types of buildings in Astana: I-515 multistorey building model and single-family residential household. The material of focus for this research is concrete inside the composition of buildings because it is the most widely used construction material. These types of buildings were chosen because they are the most frequently demolished buildings in Astana. Extensive literature reviews have demonstrated that there are previous studies regarding the construction and demolition waste stream, however there is a lack of research focused on both monetary and environmental outcomes of possible pivot from linear to circular economy practices for concrete materials in Kazakhstan. The methodology for this research is composed of the life cycle inventory analysis, i.e the gathering of the parameters of each building type as well as associated costs, life cycle assessment (LCA) and life cycle cost assessment for each end-of-life scenario and interpretation of results. LCA was performed using OneClick LCA software over the 50-years period. After the completion of necessary steps for both the I-515 building model and single-family household it was obtained that the savings from shifting from landfill disposal to the recycling of concrete fractions are 3% and 12 % respectively. Low results for the I-515 building model are explained by the enormous amount of carbon dioxide equivalent associated with this building. However, overall it was obtained that the pivoting from linear to circular economy can be beneficial for both the environment and the economy of the construction sector in Astana.
Keywords: Circular Economy; CDW Management; Life Cycle Assessment; Concrete Waste; type of access: embargo